Mutual influences on the emergence of obstruents in Coda in Brazilian Portuguese-L1 and English-L2 - Silva, Anderson Romário Souza (2025)
This study analyzes the emergence of coda obstruents in Brazilian Portuguese (BP) due to the deletion of the final post-tonic vowel (e.g., sete [sɛt]), and in English as a second language (L2) when there is no emergence of vocalic epenthesis (e.g., set [sɛt]). We examine the relationship between both phenomena in BP as the first language (L1) and in English as L2, stemming from possible mutual influences (Larsen-Freeman, 1997; De Bot et al., 2007; Beckner et al., 2009; Chang, 2019; Linck; Kroll, 2019; Opitz, 2019). We also investigate whether the Potiguar variant of BP is marked by more cases of deletion, as reported in previous research on the subject (Nascimento, 2016; Silva, 2019). For this purpose, we conducted acoustic analyses and fitted regression models to determine whether factors such as L1 variant, being bilingual, being immersion in a context where L2 is the primary language, and voicing context are factors that favor the production of coda obstruents in both languages. The results indicate that deletion is an emerging phenomenon due to the reorganization of L1 itself, without influences from L2. However, the emergence of coda obstruents in BP-L1 does not favor the production of target patterns in English-L2, as productions with coda obstruents are not challenging for Brazilian speakers.